SISTEM NOTIFIKASI DALAM HAL TERJADI PENGGABUNGAN, PELEBURAN, ATAU PENGAMBILALIHAN SAHAM PERUSAHAAN (Lex Jurnalica, 2020)
This study aims as an indication of monopolistic practices and / or unfair business competition as well as reviewing and knowing the notification system in the event of an ideal merger, consolidation or acquisition of shares so that they can function as a means of control. This research belongs to the type of qualitative research by following the typology of normative legal research, research data is collected by means of literature and document studies, relevant to the related theory and written descriptively and analyzed qualitatively. The results of this study indicate that notification of mergers, mergers or acquisition of shares can be used to determine the existence of monopolistic practices and / or unfair business competition, even though the post notification system implies that the Business Competition Supervisory Commission (KPPU) has not been able to carry out its maximum control system. . The post notification system is intended as a notification by business actors to KPPU, after the merger, consolidation, or takeover of company shares is carried out. Based on the notification, KPPU then conducts an analysis, and if the results of the analysis show that merger, merger, or takeover of company shares has the potential to cause a negative impact on competition, then the transaction must be revised or canceled. However, the revision or cancellation will become complex when the merger or consolidation of the company concerned is proven to have conducted monopolistic practices and / or unfair business competition.Â Keywords: Notification system, Monopoly, KPPU